2020
DOI: 10.1093/hmg/ddaa120
|View full text |Cite
|
Sign up to set email alerts
|

TCF12 haploinsufficiency causes autosomal dominant Kallmann syndrome and reveals network-level interactions between causal loci

Abstract: Abstract Dysfunction of the gonadotropin-releasing hormone (GnRH) axis causes a range of reproductive phenotypes resulting from defects in the specification, migration and/or function of GnRH neurons. To identify additional molecular components of this system, we initiated a systematic genetic interrogation of families with isolated gonadotropin-releasing hormone (GnRH) deficiency (IGD). Here we report thirteen families (twelve autosomal dominant, and one autosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Further, a bioinformatic screening revealed STUB1, a gene previously associated with CHH, as a putative TCF12 interactor gene. The overexpression of stub1 in tcf12 mutant zebrafish is able to restore the GnRH neuron phenotype, strongly supporting the role of TCF12 in the GnRH system [194]. 4.2.14.…”
Section: Transcription Factor 12 (Tcf12)mentioning
confidence: 67%
See 2 more Smart Citations
“…Further, a bioinformatic screening revealed STUB1, a gene previously associated with CHH, as a putative TCF12 interactor gene. The overexpression of stub1 in tcf12 mutant zebrafish is able to restore the GnRH neuron phenotype, strongly supporting the role of TCF12 in the GnRH system [194]. 4.2.14.…”
Section: Transcription Factor 12 (Tcf12)mentioning
confidence: 67%
“…Early expression studies in mouse embryos showed a strong expression of Tcf12 transcript in neurogenic areas [195] and Tcf12-null mice developed exencephaly with a high percentage of postnatal death [196]. Thus, alternative functional experiments in zebrafish demonstrated that loss of tcf12 reduced the axonal length of the terminal nerve and impaired GnRH neuron patterning [194]. Further, a bioinformatic screening revealed STUB1, a gene previously associated with CHH, as a putative TCF12 interactor gene.…”
Section: Transcription Factor 12 (Tcf12)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, TCF12, STAT1, STAT2, GATA3 and TEAD4 were significantly enriched by analysis of transcription factor binding sites. TCF12 was involved in GnRH and associated with litter size in pigs (Davis et al, 2020; Tao et al, 2013). STAT signalling was discovered by suppression of subtractive hybridization, associated with precocious puberty in goat hypothalamus and pituitary tissues (Cao et al, 2015; Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is a recent report that pathogenic TCF12 variants similar or identical to those causing CS may alternatively be associated with an apparently distinct neurodevelopmental disorder, Kallmann syndrome [gonadotrophin-releasing hormone (GnRH) deficiency associated with anosmia]. 33 This highlights a role for TCF12 in the function of GnRH neurons, with the secretion of GnRH being central to normal activity of the hypothalamicpituitary-gonadal axis. The mechanism(s) to explain the different clinical presentations associated with similar or identical TCF12 variants are currently unknown and require further investigation.…”
Section: Discussionmentioning
confidence: 99%